The Role of China’s Patriotic Hackers and Their Relationship to the Government - Rika Isnarti (Andalas Journal of International Studies (AJIS))
China is one of countries around the world known for the use of patriotic hackers who conduct many cyber-attacks. Patriotic hackers tend to be linked to nationalist movements or work for the government. For example, when ethnic Chinese were blamed for violent riots in Indonesia in 1998, Chinese patriotic hackers attacked Indonesian government websites in protest. Patriotic hackers also blocked CNN’s website during Beijing Olympics in 2008 because it reported protests in Tibet and reported bad news about China as Olympic host. They also attacked Vietnamese websites reporting conflict with China in 2014. China’s patriotic hackers struggle to control how China is represented in the cyber sphere and Chinese authorities condone their actions. There are many benefits that the government gains from patriotic hackers and it is possible that the government sponsors their actions. But there are also risks for the government. This paper assesses the role of china’s patriotic hackers.hackers. Keywords: China patriotic hacker, cyber, China government